2015
DOI: 10.1039/c5sm01996f
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide)–clay based hydrogels controlled by the initiating conditions: evolution of structure and gel formation

Abstract: The formation of the hydrogel poly(N-isopropylacrylamide)-clay (LAPONITE®) by redox polymerization was investigated, and the main factors governing the gel build-up were determined. The significant effect of the redox initiating system ammonium peroxodisulfate (APS) and tetramethylethylenediamine (TEMED) on gel formation and structure was established, making it possible to control the structure of the gel. Moreover, the pre-reaction stage involving the quality of the clay exfoliation in an aqueous suspension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 41 publications
7
50
0
Order By: Relevance
“…Primary TEMED, sulfate, and hydroxyl radicals are generated by redox initiation with KPS and TEMED 37.…”
Section: Resultsmentioning
confidence: 99%
“…Primary TEMED, sulfate, and hydroxyl radicals are generated by redox initiation with KPS and TEMED 37.…”
Section: Resultsmentioning
confidence: 99%
“…Since the inhomogeneity of polymer gels is closely related to spatial concentration fluctuations, it has been investigated with scattering methods such as light scattering, small‐angle X‐ray and neutron scattering, or by a combination of both . Several spectroscopy techniques such as nuclear magnetic resonance (NMR), ultraviolet–visible spectroscopy, Fourier transform infrared spectroscopy, and Raman spectroscopy have been utilized to study the molecular and phase evolution during formation of hydrogels . Among them, especially proton double‐quantum ( 1 H DQ) NMR has become one of the most powerful and quantitative methods .…”
Section: Introductionmentioning
confidence: 99%
“…[21,[26][27][28] Several spectroscopy techniques such as nuclear magnetic resonance (NMR), ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and Raman spectroscopy have been utilized to study the molecular and phase evolution during formation of hydrogels. [29,30] Among them, especially proton double-quantum ( 1 H DQ) NMR has become one of the most powerful and quantitative methods. [31][32][33][34][35] It addresses the 1 H-1 H dipolar couplings, which depend on the orientation of chain segments, i.e., geometry, distance, and chain dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…As to the results reported by Haraguchi et al, radicals produced by redox initiator pairs are concentrated near the surfaces of the clay layers. After initiation of NIPAAm polymerization, propagating PNIPAAm chains start to tie neighboring clay layers while Matejka et al reported that in the case of TEMED‐APS pair as redox initiator, spectroscopic characterization results proved that the interactions between TEMED molecules and clay layers were much stronger than clay‐NIPAAm and clay‐PNIPAAm interactions . Okano et al reported that the incorporation of hydroxyl end groups to PNIPAAm chains, i.e., the terminal hydrophilic modification was more effective to raise the LCST compared with their random copolymers with hydrophilic comonomers, due to strong hydrogen bonds of their free ends with water molecules .…”
Section: Resultsmentioning
confidence: 99%